Study on ethyl groups with two different orientations in [N(C2H5)4]2CuBr4. (June 2016) - Lim, Ae Ran
Abstract: The crystal structure and phase transition temperature of [N(C2 H5 )4 ]2 CuBr4 are studied using X-ray diffraction and differential scanning calorimetry (DSC); measurements revealed a tetragonal structure and the two phase transition temperatures T C of 204 K and 255.5 K. The structural geometry near T C is discussed in terms of the chemical shifts for 1 H magic angle spinning (MAS) nuclear magnetic resonance (NMR) and 13 C cross-polarization (CP)/MAS NMR. The two inequivalent ethyl groups are distinguishable by the 13 C NMR spectrum. The molecular motions are discussed in terms of the spin–lattice relaxation times T 1ρ in the rotating frame for 1 H MAS NMR and 13 C CP/MAS NMR. The T 1ρ results reveal that the ethyl groups undergo tumbling motion, and furthermore that the ethyl groups are highly mobile. Graphical abstract: Line width of 13C cross-polarization magic angle spinning (CP/MAS) nuclear magnetic resonance (NMR) in [N(C2H5)4]2CuBr4 as a function of temperature. Inset: 13C CP/MAS NMR spectrum in [N(C2H5)4]2CuBr4 at 300 K. Highlights: Structural geometry near T C . Tumbling motion. Two inequivalent ethyl (1) and ethyl (2).